Rejected Loyalty: José Antonio Arze and Moscow. Bolivia, First Half of the 20th Century - Schelchkov, Andrey (Revista de Historia Social y de las Mentalidades, 2024)
The relationship between the left-wing intellectuals and the International Communist movement, the comintern, is one of the most complicated issues in the history of the Latin American revolutionary movement. The intellectuals were more often than not disappointed with the Communists’ politics and joined the camp of their opponents but there were cases, like the bolivian José Antonio Arze, who maintained his loyalty to and admiration for the ussr and communism all his life. This fact was not really appreciated by the comintern authorities, which lead to a series of errors and failures in Bolivia, where the rejected arze created one of the most successful workers’ parties, acquiring great influence in the country in a very short time. The decision to accept Arze’s group as communist, or not, stemmed from the authorities at the Buenos Aires South American secretariat, whose attitude in many respects was based on personal animosity and the dogmatic conviction of the rectitude of their position against the declared intellectuals during the “bolshevizationË® of the parties in the region and Moscow did not question it, as it followed a policy of granting the regional authorities the right to said decisions.
Keywords: Comintern; Bolivia; José Antonio Arze; Latin American Intellectuals